Some remarks on the algebraic structure of the finite Coxeter group F4 - Muhammad A. Albar; Norah Al-Saleh (International Journal of Mathematics and Mathematical Sciences)
We consider in this paper the algebraic structure and some properties of the finite Coxeter group F4.